2021
DOI: 10.1111/jnc.15286
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐level assessment of the bidirectional relationship between aging and the circadian clock

Abstract: The daily temporal order of physiological processes and behavior contribute to the wellbeing of many organisms including humans. The central circadian clock, which coordinates the timing within our body, is located in the suprachiasmatic nucleus (SCN) of the hypothalamus. Like in other parts of the brain, aging impairs the SCN function, which in turn promotes the development and progression of aging‐related diseases. We here review the impact of aging on the different levels of the circadian clock machinery—fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 222 publications
(281 reference statements)
0
17
0
Order By: Relevance
“…Several reports have investigated the activity patterns of clock neurons during aging ( Buijink and Michel, 2021 ). For example, in aged hamsters, SCN neuronal activity deteriorated ( Watanabe et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have investigated the activity patterns of clock neurons during aging ( Buijink and Michel, 2021 ). For example, in aged hamsters, SCN neuronal activity deteriorated ( Watanabe et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in Drosophila and mammals examined how aging, from molecules to behavior, affects the circadian clock machinery ( Kondratova and Kondratov, 2012 ). In mammals, the circadian clock network shows age-related electrophysiological changes, including membrane currents and spiking activity, in the suprachiasmatic nucleus (SCN) ( Biello, 2009 ; Farajnia et al, 2014 ; Buijink and Michel, 2021 ). However, the mechanistic relationships between core-clock molecular signaling and electrophysiological function are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some cardiovascular incidents can often appear in days and manifest diurnal habits [ 16 , 17 ]. A high rush of blood pressure at early hours in the morning was noted to have an association with the development of hemorrhagic stroke and sudden cardiac deaths [ 18 , 19 ]. The increased activity of plasma renin and noradrenaline hormones in the morning hours can cause vasoconstriction in the coronary artery, thus leading to greater risk [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human and rodent studies have shown that aging affects the circadian system ( Buijink and Michel, 2021 ). While there is an age-related reduction in light sensitivity ( Lupi et al, 2012 ), melanopsin-mediated responses appear to be retained in older animals even in the absence of rods and cones ( Semo et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…While there is an age-related reduction in light sensitivity ( Lupi et al, 2012 ), melanopsin-mediated responses appear to be retained in older animals even in the absence of rods and cones ( Semo et al, 2003 ). Age-related changes have been widely reported in circadian rhythms and sleep, although there are conflicting reports as to the phenotypic effects of aging on the central clock itself ( Buijink and Michel, 2021 ). Interestingly, the circadian clock itself also affects aging: transplanting the SCN of young mice into old mice resulted not only in increased robustness of circadian rhythms ( Van Reeth et al, 1994 ), but also in an increase in life expectancy ( Hurd and Ralph, 1998 ).…”
Section: Introductionmentioning
confidence: 99%